Thirty years of the Clean Air Act Amendments: Impacts on haze in remote regions of the United States (1990–2018). (15th December 2020) - Hand, J.L.; Prenni, A.J.; Copeland, S.; Schichtel, B.A.; Malm, W.C.
Abstract: The Clean Air Act Amendments of 1990 were aimed at reducing major environmental threats in the United States, such as acid rain, urban air pollution, toxic air emissions, and regional haze. To this end, there have been major reductions in anthropogenic gaseous emissions of sulfur dioxide (SO2 ) and nitrogen oxides (NOx ). SO2 and NOx are also major contributors to particulate haze, which affects visibility in both urban and rural environments. The Interagency Monitoring of Protected Visual Environments (IMPROVE) network has tracked trends in haze in remote regions of the United States since the late 1980s by reconstructing total light extinction (bext ) from speciated particulate concentrations. Regional trends in bext were examined using aggregated data from individual sites. Regional, annual mean short-term trends analyses (2002–2018) indicated strong reductions in bext associated with reduced SO2 and NOx emissions, especially in the eastern United States (−4.3% yr −1, p < 0.001) where haze historically was dominated by sulfate particles. Less improvement occurred in the Intermountain West/Southwest (−0.9% yr −1, p = 0.03) and trends were negative but insignificant along the West Coast (−1.5% yr −1, p = 0.19). On average, across the continental remote United States, bext has decreased at a rate of −2.8% yr −1 (p < 0.001) from 2002 through 2018 and -1.8% yr −1 (p < 0.001) from 1992 through 2018. The composition of haze has shifted away from being sulfate-dominated to having higher contributions from carbonaceous and crustal aerosols. This shift points to the success of combined regulatory activities aimed at reducing anthropogenic emissions over the last three decades. As emissions from regulated sources of SO2 and NOx continue to decline, the contributions to haze from unregulated sources, both anthropogenic and natural, such as oil and gas extraction, international sources, biomass burning, and dust, have increased in importance. Reducing haze from these sources would require additional mitigation strategies and resource management plans. Graphical abstract: Image 1 Highlights: Haze trends were calculated at remote sites across the United States. Average haze across the U.S. has decreased by nearly 50% since 1992. The greatest decrease in haze in the U.S. occurred in the East.